Hästhållningen i Sverige 2009 : intervjuer med 52 hästhållare i 5 kommuner - Wallberg, Sandra (SLU/Dept. of Animal Nutrition and Management (until 231231), 2010)
The purpose of this degree project is to investigate how horse keepers reasons about horse keeping and how the horse keeping looks like today. It is interesting to compare modern horse keeping with ancien recommendations and how the horses were kept then to understand how much in the horse keeping today that is based on traditions instead of research and science. The degree project was based on data from interviews of 52 horse keepers in five different municipalities. All interviews have been based from the same questionaire about how there horses are kept today, what they think about different housing systems, how they think horses will be housed in the future and what problems they think are the biggest in horse keeping today. The results shows that single boxes indoors are the most frequently used housing system today. Most of the horse keepers are pleased with the type of housing system they are using today, thinks that single boxes indoors and loose housing systems are the most appropriate systems for the working environment and for the welfare of the horse, but single boxes are the most safety system. Most of the horse keepers think that horses will be kept in single boxes indoors or in loose housing systems in the future. The recommendations within horse keeping have changed a lot over the years, for example says mouldy hay being unagreeable for the horse today. One common tradition within horse keeping that origin from ancient recommendations from the beginning of the 1900-century is that oats is a very often used feed concentrate today, despite that the recommendations now is that the horse should satisfy as much as possible of the energy it needs from the roughage. They consider the biggest problem for horse keepers today is lack of competence or ignorance. The knowlegde that exist today need to become more available, that is something the Swedish board of Agriculture is working with today within the project viable horse business enterprise.